Program development study focusing on emotional intelligence skills of nursing students: randomized controlled trial - Yüceyurt, Nil Küçük; Kaya, Hülya (BMC nursing, 2025)
Background Emotional intelligence is crucial in nursing care. This study aimed to develop and evaluate an emotional intelligence training program based on Demirel’s Program Development Model and Bar-On EQ Model. Methods The study is a randomized controlled trial with experimental, placebo, and control groups. The study was conducted with the population of the first year students (n:250) studying in the nursing faculty of a research university. The students were randomly placed in experimental ( n = 20), control ( n = 20), and placebo ( n = 20) groups. Bar-On Emotional Quotient Inventory (EQ-i) was used to measure emotional intelligence. The intervention lasted 8 weeks. Blinding and synchronized placebo training were applied to minimize bias. The Emotional Intelligence Training Program developed, was applied as the intervention in the study. In order to minimize the risk of interaction, a different training program was synchronously applied to the placebo group. In order to create the illusion that the training initiative was the same for this group, a training initiative on environmental awareness, which is a different subject, was applied in the same number of sessions and duration. In the analysis of the data, SPSS 25 package software were employed. Results In the measurements performed following the training intervention, it was determined that the students in the experimental group had significantly higher emotional intelligence mean score compared to pre-training period mean score and the students in the placebo and control groups. The post-training emotional intelligence scores (Mean ± SD) were: Experimental group 3.66 ± 0.13, Control group 3.11 ± 0.30, Placebo group 3.35 ± 0.28. The experimental group showed significant improvement. The pre-training and post-training emotional intelligence scores (Mean ± SD) were: Experimental group: 3.22 ± 0.63 (pre), 3.66 ± 0.13 (post); Control group: 3.28 ± 0.62 (pre), 3.11 ± 0.30 (post); Placebo group: 3.51 ± 0.49 (pre), 3.35 ± 0.28 (post). The experimental group showed significant improvement ( p < 0.001, d = 1.2). Conclusions In conclusion, it was observed that the emotional intelligence training program developed and applied to the nursing students was effective in increasing total emotional intelligence scores by approximately 13.7% compared to the pre-training level. The findings indicate that the program can effectively enhance emotional intelligence in nursing students and is applicable within nursing curricula.’ Trial registration The study was conducted in line with the CONSORT diagram. The study registered ClinicalTrials.gov. ID: NCT05379361 (date: 2022-05-17).